Factors of collective reputation of the Italian PDO wines: An analysis on central Italy - Andrea Marchini; Chiara Riganelli; Francesco Diotallevi; Chiara Paffarini (Wine Economics and Policy, 2014)
As many research studies confirm, the importance of collective reputation is increasing, especially in the agro-food chain. Currently, the reputation of firms and brands is the main key driver for companies' competitiveness and success in modern markets. This paper empirically investigates the determinants of reputation of PDO wines in Central Italy. In particular, it uses the qualitative assessment expressed by the National Association of Sommeliers and proposes a synthetic indicator of reputation. By using different statistical sources, we also evaluate the impact of some variables on the reputation levels of individual PDO areas. We looked at the structural characteristics of the designation (number of producers, age of the designation, etc.), the minimum quality standards, and the characteristics of the economic vitality of the territories. The study aims to contribute to the debate on the role of the quality proposed by firms and reputation built over time.
Keywords: 330; Collective reputation; DOC wines; Italian wines; Ordered logit